Nanorods and Nanocomposites - Sasani Ghamsari, Morteza; Dhara, Soumen (IntechOpen, 2020)
The book, Nanorods and Nanocomposites aims to provide the reader with an overview of the recent advances made on the synthesis of nanorods and nanocomposites and their emerging applications for a better lifestyle. The nanorods are a surprising gift to materials science from the research field of nanoscale materials. Nanorods promise to serve as a building block of the next-generation electronic and optoelectronic devices. Nanocomposite materials are multiphase solid materials that have one organic or inorganic nanoarchitectured compound with various nanostructures, such as nanoparticles, nanowires, nanorods, and nano-films, etc., or with multiphase solid materials (metals, oxides, polymers, and carbon). Due to the progressive physical, chemical, electrical, thermal, optical, electrochemical, and catalytic properties of nanocomposites, they exhibit multi-functional characteristics in a variety of engineering applications such as piezoelectrics, thermoresistors, sensors, energy-related technologies, water purification catalysts, electro-photonics, and so on. Despite the wide variety of applications due to their unique nanostructures, the fabrication of nanocomposites and the realization of their applications in different fields remains a challenging task. The focus of this book is to provide a platform for presentation of the latest knowledge and recent progress in synthesis, functionalization, and applications of nanocomposite materials. It is expected that this book presents the most attractive and versatile technological developments in the field of nanorods and nanocomposite materials and their applications that will provide a better understanding of the currently ongoing research in related fields.